Adoption and Implementation of Self-Development IT Applications : An Empirical Study of State Islamic Higher Education Institutions in Indonesia - Muhammad Qomarul Huda; Nur Aeni Hidayah; Noor Azura Zakaria; Eva Khudzaeva (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
Implementing IT innovation in organizations is a complex and challenging process that affects organizational problems. The process involves many interacting factors and actors; hence this situation is difficult to control. This problem demonstrates the need to understand researchers' perceptions of IT adoption and implementation. This study aims to explore in depth the adoption and implementation of self-development IT applications (SDIT) in Islamic-based Higher Education Institution (IHEI) in Indonesia. The IT Adoption and Implementation Framework (Irawan et al., 2018) was applied as a lens to investigate the case. We conducted in-depth interviews with key informants involved during the adoption and implementation process in the organization. Interviews were transcribed and analyzed using thematic analysis. Certain Focus Group Discussion (FGD) studies and specific interviews with key informants representing three levels of management explained that mediating factors such as post-implementation interventions, subjective norms, and facilitating conditions influence success in adopting and implementing IT innovations in such cases. This study concludes that managerial interventions play an important role in reducing resistance from authoritarian approaches to mandating use and serve as a determinant of its sustainability in the future. These findings have significant implications for understanding how to achieve success in IT adoption and implementation in the post-implementation phase by providing empirical evidence. Theoretically, this study contributes to IT adoption and implementation frameworks by identifying the active role of critical actors in the adoption and implementation of IT applications in higher education institutions.